2009
DOI: 10.1016/j.jaci.2008.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Soybean (Glycine max) allergy in Europe: Gly m 5 (β-conglycinin) and Gly m 6 (glycinin) are potential diagnostic markers for severe allergic reactions to soy

Abstract: Sensitization to the soybean allergens Gly m 5 or Gly m 6 is potentially indicative for severe allergic reactions to soy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
217
1
14

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(242 citation statements)
references
References 31 publications
3
217
1
14
Order By: Relevance
“…While several studies have shown that IgE from soysensitive patients react primarily to the glycinin and β-conglycinin fractions (Holzhauser et al 2009;Ogawa et al 1995), we have shown in this study that a high percentage of patient IgE also reacts to non-storage proteins, including a seed maturation protein known as LEA protein. In fact, two patients in this cohort had an IgE reaction only to LEA protein (Figs.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…While several studies have shown that IgE from soysensitive patients react primarily to the glycinin and β-conglycinin fractions (Holzhauser et al 2009;Ogawa et al 1995), we have shown in this study that a high percentage of patient IgE also reacts to non-storage proteins, including a seed maturation protein known as LEA protein. In fact, two patients in this cohort had an IgE reaction only to LEA protein (Figs.…”
Section: Discussioncontrasting
confidence: 43%
“…These three subjects share a common IgE reaction against both the α subunit of β-conglycinin (#3) and the A2 subunit of glycinin (#10) (see Table 3). Holzhauser et al (2009) have recently shown that these two allergens, Gly m 5 (β-conglycinin) and Gly m 6 (glycinin), were potentially indicative for severe allergic reactions to soy in a European adult cohort. Most of the individual's serum in our study recognized between four and six soybean proteins at varying intensities.…”
Section: D Screening With Patient Seramentioning
confidence: 99%
“…Soybean is one of the most important foods causing food allergy in childhood 1 . In addition, studies have shown that allergy to soybean can be caused by IgE crossreactivity between Bet v 1, a major allergen of birch pollen, and its homologue pathogenesis-related class 10 (PR-10) protein in soybean, Gly m 4 2,3 .…”
Section: To the Editormentioning
confidence: 99%
“…Soy allergy conventionally is characterized by IgE sensitization to storage proteins like Gly m 5, Gly m 6 (Holzhauser et al, 2009;Ito et al, 2011), or Gly m 8 that are 2S albumins (Ebisawa et al, 2013). The association between birch and soy allergy was first reported by Kleine-Tebbe et al (2002) describing that patients with birch pollen allergy had allergic reactions to a soy-containing dietary product.…”
Section: Discussionmentioning
confidence: 99%